PENGEMBANGKAN MEDIA JOURNAL BESTIE UNTUK MENINGKATKAN KETERAMPILAN MENULIS SISWA KELAS IV SD SWASTA TAHFIDZ AULIA - Ruswaini, Ruswaini; Hasibuan, Ahmad Laut (Jurnal Bahastra, 2023)
As the aim of learning Indonesian at school is to develop students' language skills, both orally and in writing. Students are expected to have language skills, because language plays an important role in human life, especially in Indonesian subjects. The purpose of this research is to develop students' writing skills with bestie journal media. The method used in this research is development research. This research was conducted in class IV of Tahfidz Aulia Private Elementary School starting in January 2023. The samples used were 22 class IV Abu Bakar Ash Siddiq students and 16 class IV Umar Bin Khattab students. The instruments used in this study were media validation sheets, observation sheets on the implementation of the learning process, and assessment sheets for students' writing skills. This research is said to be successful if there is an increase in the value of students' writing skills. Based on the results of the analysis carried out in this study, it can be stated that the development of bestie journal media to improve the writing skills of fourth-grade elementary school students were declared successful by making improvements to the learning process plan, implementing the learning process and providing support to students in the form of learning motivation. The success of this study was demonstrated by the mastery of student learning in cycle II where there were 70% of students scored more than 75 which was indicated by an average value of 78.22 and a standard deviation of 3.45 which previously only had an average value of 65. 27 and a standard deviation of 3.575 with completeness in the first cycle of 63.63%.